Performance study of a simplified shape optimization strategy for blended-wing-body underwater gliders - Chengshan Li (International Journal of Naval Architecture and Ocean Engineering, 2020)
Shape design optimization for Blended-wing-body Underwater Gliders (BWBUGs) is usually computationally expensive. In our previous work, a simplified shape optimization (SSO) strategy is proposed to alleviate the computational burden, which optimizes some of the Sectional Airfoils (SAs) instead of optimizing the 3-D shape of the BWBUG directly. Test results show that SSO can obtain a good result at a much smaller computational cost when three SAs are adopted. In this paper, the performance of SSO is investigated with a different number of SAs selected from the BWBUG, and the results are compared with that of the Direct Shape Optimization (DSO) strategy. Results indicate that SSO tends to perform better with more SAs or even outperforms the DSO strategy in some cases, and the amount of saved computational cost also increases when more SAs are adopted, which provides some reference significance and enlarges the applicability range of SSO.